NEREA CALVILLO - Aeropolis. Queering Air in Toxicpolluted Worlds - Garrido López, Fermina (ZARCH, 2024)
NEREA CALVILLO Aeropolis. Queering Air in Toxicpolluted WorldsColumbia Book son Architecture and the City, New York, 2023, 285 pp. Tapa blanda. 19,50 €Idioma: inglésISBN: 978-1-941332-78-8